Detraining of specific neuromuscular qualities in elite footballers during COVID-19 quarantine. (16th November 2021) - Cohen, Daniel D.; Restrepo, Alfredo; Richter, Chris; Harry, John R.; Franchi, Martino V.; Restrepo, Carlos; Poletto, Rodrigo; Taberner, Matt
ABSTRACT: The COVID-19 pandemic forced elite football leagues into extended breaks followed by prompt resumption of competition. Inadequate periods of on-pitch football-specific training may underlie the increased injury incidence reported following restart in a non-peer reviewed report. Detraining effects from isolated training are expected, but existing models do not completely describe the unprecedented conditions imposed by COVID-19. Providing insight into specific neuromuscular qualities affected by extended absence of football-specific training, we share countermovement jump performance and kinetic data from an elite team's assessments pre and post 15 weeks of isolated training, and to contextualise these trends, off-season changes with no training. The isolated circuit resistance and aerobic interval training maintained jump height and Reactive Strength Indexmodified, but there were moderate magnitude ( p = 0.01–0.04) changes in eccentric 'yielding' and landing 'loading' phase variables. These changes suggest a compromised initiation of countermovement deceleration, impact attenuation and altered coordination/motor control strategies or muscle-tendon properties. This analysis may have revealed kinetic markers specifically stimulated by football-specific training/competition, relevant to post-quarantine monitoring. Lower landing forces may reduce overuse injury risk, while yielding phase alterations suggest a negative effect on reactive performance, therefore the overall effect on vulnerability to injury is unclear.